STRESSNI BARTARAF ETISHGA QARATILGAN PSIXALOGIK TRENINGLAR - Egamova Muqaddas Xasan qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2026)
This article analyzes stress as one of the most common psychological problems in modern society and examines its negative effects on an individual’s mental state, emotional balance, and behavior. The causes of stress and its psychological and physiological manifestations are discussed. The article also explores psychological training programs aimed at reducing stress and minimizing its negative consequences. In particular, relaxation techniques, breathing exercises, autogenic training, cognitive-behavioral methods, emotional self-regulation, and group psychological trainings are analyzed. The role of psychological trainings in enhancing stress resistance, emotional stability, positive thinking, and adaptability is emphasized. The results of the study demonstrate the effectiveness of psychological trainings in reducing stress and strengthening psychological well-being, as well as their applicability in educational institutions and practical psychological activities.